Direct silylation of Trypanosoma brucei metabolites in aqueous samples and their GC-MS/MS analysis - Podolec, Peter; Szabó, Alexandra Hengerics; Blaško, Jaroslav; Kubinec, Róbert; Górová, Renáta; Višňovský, Jozef; Gnipová, Anna; Horváth, Anton; Bierhanzl, Václav; Hložek, Tomáš; Čabala, Radomír (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2014)
A simple two-step method for the derivatization of polar compounds (lactate, alanine, glycerol, succinate and glucose) using hexamethyldisilazane (HMDS) and N,O-bis(trimethylsilyl)trifluoroacetamide (BSTFA) was developed. This method allows direct derivatization of aqueous samples wihout sample pretreatment. The method was used for the analysis of the metabolites of the unicellular organism Trypanosoma brucei. The limits of detection by GC-MS/MS analysis were in the range of 0.02 mg L(-1) for glucose to 0.85 mg L(-1) for lactate.
Keywords: Trimethylsilyl Compounds; Lactic Acid; organické sloučeniny křemíku; kyselina mléčná; Gas Chromatography-Mass Spectrometry; Limit of Detection; Reproducibility of Results; reprodukovatelnost výsledků; limita detekce; Trypanosoma brucei brucei; trimethylsilylové sloučeniny; alanin; Organosilicon Compounds; glukosa; plynová chromatografie s hmotnostně spektrometrickou detekcí; Alanine; Glucose